Electrically tunable temporal imaging in a graphene-based waveguide. (16th April 2019) - Xie, Peng; Wen, Yu; Wan, Zishen; Wang, Xinyu; Liu, Jiarui; Yang, Wenqiang; Li, Xiaofeng; Wang, Yishan
Abstract: We propose an electrically tunable temporal imaging system (TIS) based on four-wave mixing in a dispersion engineered graphene-based waveguide, which could realize a magnification factor of 1000× for a signal consisting of two 100-fs-wide pulses separated by 500 fs and a large working bandwidth of about 700 nm. The TIS was analyzed by solving the couple-mode equations in detail. It was demonstrated that the working wavelength range could be tuned via a small disturbed bias voltage applied to the graphene layer without changing the geometric structure of the waveguide. These results provide attractive insights for potential applications in integrated optics and optical communications.